Improving The Students’ Vocabulary And Creativity By Draw Story In Learning English - Minda Mora; Muhammad Fathoni (International Journal of Educational Research & Social Sciences, 2021)
The aim of this study was to improve the students’ vocabulary and creativity using Draw Story in learning English. The method of this study was classroom action research which had three cycles whereby there were two meetings for each cycle. Each cycle consisted of four steps: planning, implementing, observation and reflection. The field notes and test constituted the research data. The qualitative data were analyzed through assembling the data, coding, comparing, building interpretations, and reporting the outcomes. The quantitative data were analyzed by comparing the mean scores of the pre-test and the post- tests. The research findings showed that draw story could improve: (1) the students’ vocabulary; (2) the students’ ability in identifying the use of appropriate words; (3) the students’ ability in spelling and pronouncing the words correctly; (4) the students’ creativity in drawing.